# Quick implicit differentiation question

• Mar 2nd 2011, 04:45 PM
Combinatus
Quick implicit differentiation question
The problem is stated as follows:

---

Show that the equation $zx^2y^3 + (x+y)e^{z-x}-x^2-x-4y=-3$ defines z as a function of x and y near (1,1,1). Also show that (1,1) is a stationary point of this function and determine its kind.

---

The first part is easily shown with the implicit function theorem.

Differentiating the equation implicitly with respect to x:

$2xy^3z + x^2y^3\frac{\partial z}{\partial x} + e^{z-x} + (\frac{\partial z}{\partial x} -1)(x+y)e^{z-x} -2x -1 = 0$, so $(x,y,z(x,y)) = (1,1,1)$ gives $2 + \frac{\partial z}{\partial x} + 1 + 2(\frac{\partial z}{\partial x} - 1)-2-1=0$ near (x,y) = (1,1), and consequently, $\frac{\partial z}{\partial x} = \frac{2}{3}$ there.

Thus, (x,y) = (1,1) isn't a stationary point as the problem claims.

Feel free to point and laugh at me and tell me that (or preferably why) my arithmetic is wrong.
• Mar 3rd 2011, 02:49 AM
HallsofIvy
Looks to me like you are correct. I also get $z_x= \frac{2}{3}$ at (1, 1).